Matching stage strategy development of PT Alam Sutera Realty Tbk: Diversification as key strategy for business sustainability - Gunawan, William Ben (Review of Management, Accounting, and Business Studies, 2024)
This study investigated the strategic development of PT Alam Sutera Realty Tbk (ASRI), focusing on diversification as a key strategy for business sustainability amidst issues of undervalued stock and unstable financial performance. A comprehensive analysis of external and internal factors was conducted using frameworks such as PESTLE, Porter’s 5 Forces, Internal-External Matrix, TOWS Matrix, SPACE Matrix, Grand Strategy Matrix, Quantitative Strategic Planning Matrix (QSPM), Blue Ocean Recommendation, and Balanced Scorecard. The findings indicated that ASRI scored 3.21 on the Internal Factor Evaluation (IFE) and 3.29 on the External Factor Evaluation (EFE), placing it in the "Grow and Build" quadrant of the SPACE Matrix. This suggested strategies such as forward, backward, and horizontal integration, market penetration, market development, and product development. The Grand Strategy Matrix, supported by Competitive Profile Matrix (CPM) scores and industry growth data, advocated for diversification or new venture formation through joint ventures. QSPM analysis identified Product Development in Vertical Buildings and Sustainable Housing as ASRI’s most attractive and promising strategies. Vertical building development optimized land use and met rising urban market demands, while sustainable housing appealed to the environmentally conscious segment. Future recommendations for ASRI included increased investment in research and development, partnerships with green technology firms, and continuous market trend monitoring to ensure strategic relevance and effectiveness in the evolving real estate industry. This diversified approach aimed to leverage new market opportunities and strengthen ASRI’s market position through strategic expansion and collaboration.